The seers - Russell, Bailey J. (Russell, Bailey J. Haunting of Hawthorne Harbor, 2021)
Mary Paine starts her junior year of high school estranged from her best friend James, grieving the death of her brother Paul, and seeing people who are not there. A mysterious group of teens befriends her and tells her she is like them--a seer--someone who can see ghosts. The new friends help her understand her ability and explain their purpose.